Common English writing errors made by English major students at Hung Yen University of Technology and Education and the significance of correcting errors to English writing teaching - Nguyen, Thi Duyen (University of Languages and International Studies, 2017)
This paper studies the common written errors that first year English major students in Hung Yen University of Technology and Education make and the significance of error correction in English writing teaching. To achieve the desired aims of the current stu (...)